The Effect of the Different Types Plants on the Recirculating Aquaculture System (RAS) on the Growth Performnace of Carp Seed (Cyprinus carpio) - Raihan Wandri Samara; Iskandar Iskandar; Evi Liviawaty; Roffi Grandiossa (Jurnal Perikanan dan Kelautan, 2022)
Intensification of culture through stocking densities and high feeding rates can cause water quality problems. Utilization of the recirculation system in intensive cultivation is important to maintain water quality. This study aims to determine the best type of aquatic plants in RAS for the growth of carp fish seeds. The research in January - February 2021. The test fish used were carp fish with a length of 6 - 7 cm and a weight of 3 - 5 gr. The feed used is commercial feed with a protein content of 31 - 33%. Feeding was carried out at 08.00 A.M and 04.00 P.M  with 3% fish biomass. This study used an experimental method with CRD with 4 treatments and 3 replications. Treatment A (Control, without plants), treatment B (cotton fiber, bio balls, activated charcoal and kale), treatment C (cotton fiber, bio balls, activated charcoal and watercress plants) and treatment D (cotton fiber, bio balls, activated charcoal and pakchoy plants). The results showed that the use of different aquatic plants had a significant effect (P <0,05) on SR, SGR, length growth and absolute weight, plant height, and a number of leaves, but no significant effect (P> 0,05) on FCR. The best treatment in this study was B with an SR value of 82,22 ± 7,70%, SGR 4,08 ± 0,14%, absolute length 4,97 ± 0,27 cm, absolute weight 15,81 ± 1,96 gr, plant height 60,67 ± 18,01 cm, number of leaves 20,42 ± 9,66 leaves and FCR 1,10 ± 0,0896